Instrumentation for localized superconducting cavity diagnostics. (12th January 2017) - Conway, Z A; Ge, M; Iwashita, Y
Abstract: Superconducting accelerator cavities are now routinely operated at levels approaching the theoretical limit of niobium. To achieve these operating levels more information than is available from the RF excitation signal is required to characterize and determine fixes for the sources of performance limitations. This information is obtained using diagnostic techniques which complement the analysis of the RF signal. In this paper we describe the operation and select results from three of these diagnostic techniques: the use of large scale thermometer arrays, second sound wave defect location and high precision cavity imaging with the Kyoto camera.